Which of the following is the correct factored form of the given equation? x^2 – x = 6 (x + 3)(x + 2) = 0 (x + 3)(x – 2) = 0 <

Question

Which of the following is the correct factored form of the given equation? x^2 – x = 6
(x + 3)(x + 2) = 0
(x + 3)(x – 2) = 0
(x – 3)(x + 2) = 0
(x – 3)(x – 2) = 0

in progress 0
Audrey 2 weeks 2022-01-08T08:21:32+00:00 1 Answer 0 views 0

Answers ( )

    0
    2022-01-08T08:23:03+00:00

    Answer:

    (x – 3)(x +2) = 0

    Step-by-step explanation:

    multiply it or just find the zeros of the function it become 3&-2

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )